Why Barriers to Entry Are Barriers to Understanding - Carlton, Dennis W (American Economic Review, 2004)
The views expressed herein are those of the author(s) and not necessarily those of the National Bureau of Economic Research. ©2004 by Dennis W. Carlton. All rights reserved. Short sections of text, not to exceed two paragraphs, may be quoted without explicit permission provided that full credit, including © notice, is given to the source.